Diversity of airway epithelial cell targets for in vivo recombinant adenovirus-mediated gene transfer. - Mastrangeli, A (1993)
A variety of pulmonary disorders, including cystic fibrosis, are potentially amenable to treatment in which a therapeutic gene is directly transferred to the bronchial epithelium. This is difficult to accomplish because the majority of airway epithelial cells replicate slowly and/or are terminally differentiated. Adenovirus vectors may circumvent this problem, since they do not require target cell proliferation to express exogenous genes. To evaluate the diversity of airway epithelial cell targets for in vivo adenovirus-directed gene transfer, a replication deficient recombinant adenovirus containing the Escherichia coli lacZ (beta-galactosidase [beta-gal]) gene (Ad.RSV beta gal) was used to infect lungs of cotton rats. In contrast to uninfected animals, intratracheal Ad.RSV beta gal administration resulted in beta-gal activity in lung lysate and cytochemical staining in all cell types forming the airway epithelium. The expression of the exogenous gene was dose-dependent, and the distribution of the beta-gal positive airway epithelial cells in Ad.RSV beta gal-infected animals was similar to the normal cell differential of the control animals. Thus, a replication deficient recombinant adenovirus can transfer an exogenous gene to all major categories of airway epithelial cells in vivo, suggesting that adenovirus vectors may be an efficient strategy for in vivo gene transfer in airway disorders such as cystic fibrosis.